Aflatoxins in the nut chains: strategies to reduce their impact on consumer health and economic losses - Chulze, S.; Alaniz Zanon, M.S.; Taniwaki, M.H.; Tsitsigiannis, D.; Olsen, M.; Ortega-Beltran, A.; Herrera, M.; Vargas, E.; Logrieco, A.; Battilani, P. (Walter de Gruyter GmbH, 2024)
The presence of Aspergillus section Flavi and aflatoxins (AFs) in nut chains are of great concern due to the toxic effects of AFs on human and animal health as well as the economic losses during commercialisation. Extreme events related to climate change like increased temperature, severe rainfalls and droughts are modulating factors of fungal growth and mycotoxin production. The Expert Working Group (EWG) on nuts that worked under the frame of the Horizon 2020 Mycokey Project prepared this review based on discussions about the situation of contamination with AFs in nuts and the available strategies to reduce the impact of these toxins in the nut chains. The EWG selected as examples peanuts, pistachios and Brazil nuts, and discussed in the review the importance of nut value chains in the production, commercialisation and regulations that establish maximum levels for AFs. Also data on the Rapid Alert System for Food and Feed (RASFF) was considered and showed several notifications for mycotoxins, mainly AFs for nuts and nut products, such as pistachio nuts and dried mix nuts. Under a scenario of climate change, we elaborated strategies to prevent AFs contamination with emphasis on biocontrol and decision support systems. Also, the relevance of strategies to prevent and reduce both fungal infection and AFs accumulation in peanuts, Brazil nuts and pistachio are included as guidelines.